Health Education is a Key Pillar in Reducing Prevalence of Typhoid among Febrile Patients in Peri-Urban Western Uganda: A Cross-Sectional Study - Kiwungulo, Benard; Pius, Theophillus; Nabaasa, Saphurah; Kiconco, Ritah; Amanya, Geofrey; Amongi, Christine; Tamale, Andrew; Ruhinda, Nathan; Blessing, Yashim J. S.; Atuheire, Collins (International Journal of Scientific Study, 2017)
Typhoid has remained a public health burden leading to several morbidities and despite many attempts. Health education targeted to patients receiving care in health centers may significantly reduce burden of typhoid among febrile patients in Uganda. Material and Methods: We consecutively sampled 283 participants presenting with febrile symptoms. Consent/assent was administered and after fully understanding the study, blood samples were collected using a 2 ml syringe and transferred into red top vacutainer before laboratory tests. We carried out centrifugation at 1000 rpm for 15 min. We performed slide agglutination test to identify presence of Salmonella typhi antibodies followed by tube agglutination for quantification. Titers of <1:160 were considered positive for typhoid. Data were analyzed descriptively as medians and proportions using STATA 14. Robust Poisson regression was carried out to obtain both crude and adjusted prevalence ratios (aPR) for bivariate and multivariate analysis, respectively. Results: The median age for participants was 25 years. The seroprevalence of typhoid was 26.5% (95%, confidence interval [CI]: 21.7-32.0). Teenagers were 3 times more likely to be tested positive for typhoid compared to those below 13 years; (crude prevalence ratio = 2.76, 95%, CI: 1.11-6.83). Participants who reported to have received health education over past 2 months were 58% less likely to suffer from typhoid compared to those that reported no recent health education (aPR = 0.42; 95%, CI: 0.26-0.69). Having history of typhoid over the past 2 months was positively associated with reoccurrence of typhoid (aPR = 1.75, 95%, CI: 1.12-2.72). Conclusion: Burden of typhoid still persists in rural communities especially among teenagers. Lack of health education predisposes communities. People who have had typhoid in the past 2 months are mostly likely to have a reoccurrence of the disease.
Keywords: Febrile patients; Health education; Seroprevalence; Typhoid